A study on the feasibility of delivering a psychologically informed ward‐based intervention on an acute mental health ward. (5th May 2021) - Raphael, Jessica; Hutchinson, Taryn; Haddock, Gillian; Emsley, Richard; Bucci, Sandra; Lovell, Karina; Edge, Dawn; Price, Owen; Udachina, Alisa; Day, Christine; Cross, Catherine; Peak, Craig; et al.
Abstract: Acute mental health inpatient wards have been criticized for being nontherapeutic. The study aimed to test the feasibility of delivering a psychologically informed intervention in these settings. This single‐arm study evaluated the feasibility of clinical psychologists delivering a ward‐based psychological service model over a 6‐month period on two acute mental health wards. Data were gathered to assess trial design parameters and the feasibility of gathering patient/staff outcome data. Psychologists were able to deliver key elements of the intervention. Baseline staff and patient participant recruitment targets were met. However, there was significant patient attrition at follow‐up, with incorrect contact details on discharge being the primary reason. Implementation of a ward‐based psychological intervention appears feasible when implemented flexibly. It is feasible to recruit staff and patient participants and to collect staff outcome measures over a 6‐month period. However, greater efforts need to be taken to trace patient movement following discharge.